Monitoramento de slope streaks marcianos no Nordeste de Lycus Sulci, em Diacria - Santos Júnior, Christiano Ribeiro dos (2022)
Slope streaks are dark features found in low latitude regions of Mars formed from rapid duration events in low thermal inertia terrain. The sudden appearance of low I/F patches followed by gradual whitening are planet-relevant environmental indicators. The present work aims to quantify the variation in the lightening of slope streaks using HiRISE/MRO images. To this end, the I/F difference of 31 tracks north of Mount Olympus, arranged in 16 images dated from 2007 to 2021, served as the basis for measuring the formation and whitening of the tracks in the region. Each internal sample was subtracted by the nearest corresponding external sample with the same elevation. Tests of normality, variance, and Welch's t-test of the tracks show that the differences in the lightening and darkening of the tracks are significant and do not follow a downward trend, but a stochastic one. The tracks showed a well-defined and uniform pattern of clearing and formation during the autumns in the northern hemisphere. This mechanics is correlated to the rates of sediment deposition and suspended dust column, which supports the line of thought that the tracks are formed from dry events such as dust avalanche.